Conocimientos y actitudes sobre anticoncepción de emergencia en estudiantes de la carrera de Enfermería de la Universidad Nacional de Loja - Castro Yanangomez, Mariuxi Lizbeth (2022)
Emergency contraception is a method of contraception used to prevent unwanted pregnancy immediately after unprotected sexual intercourse, therefore, it was proposed to carry out the present study whose objective was to analyze knowledge and attitudes about emergency contraception in students of Nursing at the Universidad Nacional de Loja, for the implementation of educommunicational actions. It was a quantitative – descriptive and cross-sectional study, a survey was applied to 185 students enrolled in the academic period April - September 2021. The results showed that 79% are female, 94% are single, 54% are in the age range of 21- 25 years and 22% are in the seventh academic year. In relation to the knowledge, it was possible to determine that the students know the concept (79%), indications (74%) and place of obtaining the EC (77%), composition (62%), correct dose (52%), administration scheme (54%) and side effects (84%) of the Yuzpe method, however, a considerable group has a great lack of knowledge about the Levonorgestrel method. Regarding attitudes, the majority of respondents reject that EC protects against sexually transmitted infections, including HIV/AIDS (73%). Concluding that students have basic knowledge about emergency contraception and most have an attitude of rejection towards various EC claims; finally, considering the results presented, edu-communicational actions targeted at the study group with the aim of strengthening knowledge and attitudes of the same